Design an NDT sensor for railway foot crack detection - Ong, Jun Kai (Nanyang Technological University, 2023)
A microstrip coil antenna is presented for the detection of cracks in railway through the electromagnetic system as a form of transmitter. The fundamental is derived through having the microstrip coil antenna be induced, generating electromagnetic fields that will be optimized through different coil topologies for the analysis of defects found within the rail. The microstrip coil antenna is enclosed within a box for securing purposes, back with ferrite material to allow better transmission of electromagnetic field for detection of defects. The extend of coiling will be studied to understand the impact on the magnetic field generation. Studies will be performed through simulations on ANSYS software to understand the design systems practicality. Due to the compact size and inexpensiveness of the proposed microstrip coil antenna, it will allow further physical experiments to be done efficiently.